Glucocorticoids and body fat associated with renal uric acid and oxalate, but not calcium excretion, in healthy children - Shi, Lijie; Berkemeyer, Shoma; Buyken, Anette E.; Maser-Gluth, Christiane; Remer, Thomas (Metabolism, 2010)
In patients with hypercortisolism, who are frequently obese, the prevalence of elevated urinary excretion rates of the potential lithogenic factors (calcium, oxalate, and uric acid) is increased. We examined whether the 24-hour urinary excretion rates of calcium, oxalate, and uric acid are already associated with body fat and endogenous glucocorticoids in healthy free-living children, taking relevant nutritional and acid-base factors into account. Urinary analyte excretions were determined in 24-hour urine samples of 300 healthy children aged 4 to 14 years. Potentially bioactive free glucocorticoids were assessed as urinary free cortisol + urinary free cortisone. Associations of glucocorticoids and percentage body fat with the outcome variables were examined in regression models adjusted for sex, height, growth velocity, urinary volume, net acid excretion, and relevant nutritional factors. Percentage body fat and urinary free cortisol + urinary free cortisone explained most of the growth-independent variation of urinary uric acid and also a relevant part of oxalate, but none of calcium. Net acid excretion, an indicator of endogenous acid production, and dietary protein, salt, and fiber intakes were also variably associated with the outcomes urinary calcium, oxalate, and uric acid. In conclusion, body fatness and potentially bioactive free glucocorticoids (even in the physiologic range) appear to affect urinary excretion rates of oxalate and uric acid, whereas urinary calcium output is more strongly related to dietary factors in healthy children. Our data provide the first in vivo-based evidence that the obesity- or hypercortisolism-associated urolithiasis may be a pathophysiologic continuation of the corresponding endocrine metabolic variations in healthy children.